The impact of the Common European Framewrk of reference on teaching and testing in the Slovak Republic - Hodunko, Liudmyla (ScienceRise: Pedagogical Education, 2017)
The article examines the influence of the Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFR) on teaching and testing foreign languages in the Slovak Republic. The CEFR defines six reference levels of the language proficiency, which allows the learners’ progress to be measured at each stage of learning. Many training sessions were organized aimed at familiarization with the scales, levels and descriptors. The goal of foreign language teaching became communicative ability. Competence-based teaching, learning and assessment became popular with foreign language teachers. The attention is focused on the need to reform school final exams. The implementation of the CEFR fostered the interest of the Slovak language professionals to relate curricula and syllabi to the CEFR levels to achieve educational goals in the process of learning foreign languages. The CEFR set out the range of options for learning objectives, about syllabus design, classroom methodology and testing. Also the new Slovak curricular documents are based on the CEFR. The article considers the school-leaving examination reform in Slovakia as part of a research project, conducted in 2008, and the first attempts to relate the national examination in English to the CEFR levels. This procedure is not very easy and needs a lot of effort and a serious approach to validate the claim. The CEFR is mentioned in foreign language training at universities